2015
DOI: 10.1177/0081246315575648
|View full text |Cite
|
Sign up to set email alerts
|

South African clinical psychology’s response to cultural diversity, globalisation and multiculturalism: a review

Abstract: This article reviews responses of South African clinical psychologists to multicultural issues within an increasingly diverse and globalised context. Psychological perspectives on diversity, multiculturalism, and globalisation are presented initially as background to a review of multicultural and cross-cultural clinical psychological research conducted within the South African context. The discussion is located within the context of South African psychologists’ historical response to multicultural issues, with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 77 publications
1
5
0
Order By: Relevance
“…The HSP scale was designed and psychometrically assessed in largely homogeneous samples. We aimed to address this limitation by assessing the HSPS in South Africa, which is both ethnically diverse and has good representation of idiocentric and allocentric cultures (Burgess et al 2002;Johnston 2015). While most of our findings served to support previously published claims, EFA of our data revealed a fivefactor solution that has, to our knowledge, never been previously reported.…”
Section: Discussionsupporting
confidence: 50%
“…The HSP scale was designed and psychometrically assessed in largely homogeneous samples. We aimed to address this limitation by assessing the HSPS in South Africa, which is both ethnically diverse and has good representation of idiocentric and allocentric cultures (Burgess et al 2002;Johnston 2015). While most of our findings served to support previously published claims, EFA of our data revealed a fivefactor solution that has, to our knowledge, never been previously reported.…”
Section: Discussionsupporting
confidence: 50%
“…Furthermore, in a culturally and linguistically diverse country like South Africa (Johnston, 2011), training should reflect the equitable representation of the country's diversity. Pillay and Siyothula (2008) found that 14% of clinical psychologists in the Health Professionals Council of South Africa register were Black Africans and were trained post-1994.…”
Section: Training Issues and Challenges For Psychologists In Non-urba...mentioning
confidence: 99%
“…Assessment settings are also identified as unsuitable and test materials are limited. There also exists a shortage of practitioners to develop new tests for the multi-cultural South African population (Foxcroft & Davies, 2008;Johnston, 2015;Laher & Cockcroft, 2013;Seedat & Mackenzie, 2008).…”
Section: Transformation Agenda and Implications For Career Training A...mentioning
confidence: 99%